Critique and Analysis of the Textbook “Comparative Education: Foundation, Principles and Methods” - abbas madandararani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In recent decades, the educational competitions have increased scholars’ attention to understand the educational changes and innovations as well as ways of solving challenges in other societies. The main mission of comparative education is a critical study of the educational similarities and differences among societies and cultures. Accordingly, the attention to comparative education and its necessity have become a common phenomenon in higher education institutions which can be seen through establishments of graduate courses, research centers, and publication of books and articles. In Iran, comparative education is provided as a three-unit course in the field of educational sciences (different branches) and for undergraduate, graduate, and doctoral students. Writing and preparation of the book "Comparative Education: Foundation, Principles and Methods " shows a deliberate attempt to present this science with respect to its theoretical foundations and principles. In this paper,  the form and content of the book and rating its privileges and shortcomings are analyzed. Due to the size and pages, this book has largely made readers familiar with the general and basic framework of comparative education science. Meanwhile the most important weakness of the present work can be a lack of attention to current contemporary intellectual of comparative education.